‘Ambrosio’ Taylor Coleridge: Investigating Three Issues in Banning The Monk - Lantz, Derek (MacEwan University Student eJournal, 2024)
This paper investigates the banning in 1897 of Matthew Lewis's novel The Monk, taking special interest in the dismissal of the text by Samuel Taylor Coleridge. Sources reveal how British decency laws and the French Revolution together create a public repression which the Gothic novel both threatens and relieves in the 1890s. By highlighting journalistic reliance on Gothic terminology, the paper argues that banning art to protect citizenry is often a result of public insecurity rather than immoral content.